AGE AND PETROGENESIS OF DOLERITES ON THE MARA RIVER (SAYAN MARGINAL UPLIFT OF THE BASEMENT, SOUTHERN PART OF THE SIBERIAN CRATON) - I. А. Izbrodin; А. G. Doroshkevich; А. B. Kotov; Е. B. Salnikova; А. E. Izokh; Е. F. Letnikova; А. V. Ivanov (Геодинамика и тектонофизика, 2024)
This work focuses on petrological-and-geochemical features, as well as age of dolerites widespread within the basins of the Mara, Kamenka and Uvat rivers. The isotope geochronological data acquired for baddeleyite allowed referring origination of these rocks to the time interval 1600–1620 Ma, interpreted as the time of their emplacement. It was ascertained, that the age of dolerites represents particular geological event proceeding independently of formation of Neoproterozoic Nersinsk gabbro-dolerite complex. The Sm-Nd isotope signature indicates that parent melt generated from the metasomatic lithosphere mantle.